PENGUASAAN KONSEP SISWA PADA MATERI EKOSISTEM MELALUI PENERAPAN MODEL PROBLEM POSING LEARNING BERBASIS DONGENG SAINS (PPL-DS) - Fitri, Jaelani; Sa’adah, Sumiyati; yusup, iwan ridwan (Jurnal BIOEDUIN, 2019)
This research generally is aimed to recognize the students’ concept mastery on ecosystem material by using the Problem Posing Learning (PPL) based on science fables and its influence on the students and student responses and delays in learning were carried out using the PPL-DS model. The research method used is quasi-experimental method. Moreover, the research design used in this current research is nonequivalent control and samples were taken by purposive sampling technique. Test, questionnaire, and observation sheet are used as the instruments. Research data analysis includes several tests such as normality, homogeneity, hypothesis, and N-Gain. Data were obtained from 20 questions for each pretest and posttest. The result gained from the class using the research model has moderated criteria with an N-gain average of 0.35 while the class with non-research model has a low criterion with an N-gain value of 0.21. The implementation of activities carried out by students and teachers is fairly good with 84.21% and 88.23% achieved. The response shown by students is also quite satisfactory with a value of 86.20% high criteria. It can be concluded that there is a significant influence on the mastery of students' concepts in ecosystem material using the fairytale-based problemThis research generally is aimed to recognize the students’ concept mastery on ecosystem material by using the Problem Posing Learning (PPL) based on science fables and its influence on the students and student responses and delays in learning were carried out using the PPL-DS model. The research method used is quasi-experimental method. Moreover, the research design used in this current research is nonequivalent control and samples were taken by purposive sampling technique. Test, questionnaire, and observation sheet are used as the instruments. Research data analysis includes several tests such as normality, homogeneity, hypothesis, and N-Gain. Data were obtained from 20 questions for each pretest and posttest. The result gained from the class using the research model has moderated criteria with an N-gain average of 0.35 while the class with non-research model has a low criterion with an N-gain value of 0.21. The implementation of activities carried out by students and teachers is fairly good with 84.21% and 88.23% achieved. The response shown by students is also quite satisfactory with a value of 86.20% high criteria. It can be concluded that there is a significant influence on the mastery of students' concepts in ecosystem material using the fairytale-based problem